2010
DOI: 10.2478/s11532-009-0093-0
|View full text |Cite
|
Sign up to set email alerts
|

Cloud point extraction and preconcentration of gold in geological matrices prior to flame atomic absorption determination

Abstract: Brilliant green was used as a complexing agent in cloud point extraction (CPE) and applied for selective preconcentration of trace amounts of gold in geological matrices. The analyte in the initial aqueous solution was acidified with hydrochloric acid (0.1 M) and octylphenoxypolyethoxyethanol (Triton X-114) was added as a surfactant. After phase separation, based on the cloud point separation of the mixture, the surfactant rich phase was diluted with methanol and the analyte determined in the surfactant rich p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…It reacts with alizarine red S, forms brown precipitate and consumes the ligand. This effect was reduced, when 0.1 M of ascorbic acid was added [17]. Ascorbic acid reduces Fe(III) to Fe(II) and prevents its reaction with ligand.…”
Section: Interferencesmentioning
confidence: 91%
See 2 more Smart Citations
“…It reacts with alizarine red S, forms brown precipitate and consumes the ligand. This effect was reduced, when 0.1 M of ascorbic acid was added [17]. Ascorbic acid reduces Fe(III) to Fe(II) and prevents its reaction with ligand.…”
Section: Interferencesmentioning
confidence: 91%
“…It was found that 0.6 M of HNO 3 was optimal. A volume of 200 mL of methanol (containing 0.6 mol L À1 HNO 3 ) was added to surfactantrich phase to ensure a sufficient volume of sample for aspiration [17].…”
Section: Effect Of Diluentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct determination of gold by most of the analytical techniques suggested is to extend some problems becasue of the interfering matrix components at high concentrations in several real samples, therefore, an effective sample pretreatment step, such as preconcentration of the analyte and matrix isolation, are still necessary to obtain reliable results. Many preconcentration and separation methods have been frequently carried out using liquid-liquid [11][12][13] and liquid-solid extractions.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of the surfactant has an important influence in determining the efficiency of the extraction according to the cloud point extraction method, because its important stems from maximizing extraction efficiency by minimizing the phase volume ratio (V s /V a ), thus improving its perconcentration ability 26 . To illustrate this role, the effect of the triton x-114 concentration on the absorbance of the extracted Fe(III) -NOR complex was studied within the surfactant volume range of 0.1-2 mL of 10% (v/v) triton x-100 and keeping other variables constant.…”
Section: Effect Of Triton X-114 Amountmentioning
confidence: 99%